2016
DOI: 10.1007/s11255-016-1290-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vitamin D deficiency in calcium stone-forming patients

Abstract: Calcium stone-forming patients have lower mean levels of vitamin D and a higher percentage of hypovitaminosis D than in non-stone-forming patients. This was only related to increased iPTH levels, with urine calcium and other lithogenic parameters having no obvious effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…After full-text analysis, another 19 studies were excluded for the following reasons: 14 had no control group and no useful data, three did not provide standard deviations, and two reported duplicate data. Finally, 32 studies fulfilled our eligibility criteria and were enrolled in the meta-analysis [10,11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After full-text analysis, another 19 studies were excluded for the following reasons: 14 had no control group and no useful data, three did not provide standard deviations, and two reported duplicate data. Finally, 32 studies fulfilled our eligibility criteria and were enrolled in the meta-analysis [10,11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…The subjects were on a free or normal calcium diet in some studies [10,11,19,21,22,26,28,29,32,35,36,39,43], while restricted calcium diets were adopted in some others [24,27,31,33,34,38]. Nineteen of the included trials only tested serum/plasma 1,25(OH) 2 D [19,20,22,24,26,27,28,30,31,32,33,34,35,36,37,38,39,42,43], six only assessed 25(OH)D [18,25,40,41,44,47], and the others evaluated the two metabolites at the same time [10,11,21,22,29,45,46]. The most commonly used measurement method for 1,25(OH) 2 D and 25(OH)D was radioimmunoassay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between vitamin D status and the hematuria, another important parameter of kidney disease other than proteinuria, has not been evaluated yet. Furthermore, there are accumulating evidence that vitamin D deficiency contributes to pathologic conditions that can be presented as hematuria such as urinary stone [22], infection [23] and malignancy [24]. The present study is the first to examine this correlation using data of a nationwide population-based survey, stratified by sex and menopause status as these parameters are known to be important in analyzing the effects of vitamin D deficiency [25, 26].…”
Section: Introductionmentioning
confidence: 95%
“…It has also been shown that hypovitaminosis D may be associated with increased kidney stone formation. There is a high prevalence of vitamin D deficiency in stone formers compared to non‐stone formers . Possible explanations for this association include: secondary hyperparathyroidism in vitamin D deficiency, dietary factors (low calcium intake), increased oxidative stress or inflammation in vitamin D deficiency.…”
mentioning
confidence: 99%